The Benefit of Hedgerow Access on the Health and Growth Rate of Pasture Raised Broiler Chickens - Delgadillo, Eilea; Glidden, Caroline; Pollak, Marissa; Rysenga, Holly; Jolles, Anna; Beechler, Brianna (Frontiers in Animal Science, 2021)
Pasture rearing is an increasingly common option for small farms to produce humanely raised poultry products for an expanding market, however profit margins tend to be much lower for pastured poultry producers than for those that opt for conventional indoor rearing. Research into simple methods to optimize the growth and health of pasture-raised poultry can help small farmers maximize meat yields and decrease the morbidity and mortality of their flock, ultimately leading to higher profit margins and improved animal welfare. The objective of this study was to measure how the inclusion of mature, native foliage into pastures can impact the production performance and overall health status of two different popular breeds of commercial broiler chickens; fast-growing Cornish cross and slower growing Red rangers. During the finisher phase (30-78 days old), pastured chickens were separated by breed into either a treatment population with access to a mature bordering hedgerow, or a control population without access to a hedgerow. Weekly weight gain, daily feed intake and basic hematologic values were used to evaluate differences in the production performance and health status between each population. We found that hedge access led to a significant improvement in the rate of gain of the Cornish cross without an associated increase in feed intake, suggesting that the addition of hedges can increase meat yields in fast-growing broilers without increasing feed costs. Red rangers with hedge access demonstrated an improved ability to neutralize bacterial pathogens in whole blood and a lesser degree of hemodilution compared to control populations, suggesting improved immune function and a lower degree of heat stress in these populations . We conclude that the addition of natural environmental enrichment such as mature foliage to grass pastures can lead to improved production performance in fast-growing broilers and improvements in the health and immune function of slower growing broiler chickens.